(untitled) (American Journal of Islam and Society, 2006)
The more things change, the more they stay the same. Any reader of Michael Provence’s study of the Great Syrian Revolt of 1925 might be forgiven such cynicism. Here is a fine and well-documented example of an earlier attempt by a western power to come to grips with the Middle East – with unfortunate results. It involved foreigners infallibly confident in themselves and their mission, compliant local elites out for self-aggrandizement, insurgents preaching religious-inflected nationalism, the gulf between all three, and the ensuing horror. The Great Syrian Revolt was a pivotal event both for Syria and for Arabs at large. It allowed the former to conceptualize themselves as a nation while serving as an exemplar for the latter, thereby playing a formative role in the development of national consciousness in the region. By influencing the Baathist movement two decades later, it had ramifications far beyond its failure. Provence devotes much of the first chapter to staking out interesting theoretical ground. Rejecting the notion of insurrection as being largely a battle of ideas directed by intellectuals, he argues persuasively for an approach to the rebellion centered on a rural, rather than an urban, setting and for a casus belli founded on French misrule and economic relations between differing classes of Syrian society. His central thesis is that the grain trade between the Druze in the fertile Hawran region of southern Syria and middle-class merchants, mostly from the Maydan quarter of Damascus, was the central axis upon which the revolt turned. Such an approach has its drawbacks, namely, the paucity of documentary evidence from contemporary rural Syria. Much of the latter half of the first chapter is devoted to this difficulty. In casting a judicious eye over the range of primary source material, both French and Arabic, Provence ...